Leptomischus anisophyllus (Argostemmateae: Rubiaceae), a new species from Vietnam - Anh, Tran Thi Phuong; Quang, Bui Hong; Nuraliev, Maxim S.; Nguyen, Khang Sinh; Averyanov, Leonid V. (Phytotaxa, 2021)
Leptomischus anisophyllus, a new species of Rubiaceae, is described and illustrated, and its conservation status is discussed. The species was discovered in 2017 during a botanical survey of Pu Mat National Park (Nghe An Province, Central Vietnam). The new species is remarkable by its anisophylly, a rare feature in Leptomischus. Besides, Leptomischus anisophyllus differs from morphologically similar congeners by the following features: stems terete, pubescent when young, flowers distylous, corolla tube 10–15 mm long. An updated key to the Vietnamese species of Leptomischus is provided.